2016
DOI: 10.5195/jmla.2016.68
|View full text |Cite
|
Sign up to set email alerts
|

Research engagement of health sciences librarians: a survey of research-related activities and attitudes

Abstract: Introduction:The extent to which health sciences librarians are engaged in research is a little-studied question. This study assesses the research activities and attitudes of Medical Library Association (MLA) members, including the influence of work affiliation.Methods: An online survey was designed using a combination of multiple-choice and open-ended questions and distributed to MLA members. Responses were analyzed using descriptive statistics, content analysis, and significance testing. The authors used sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…The survey topic included terms that were seemingly related to decision making, like assess and determine, implying that a primary motivation of librarians who undertook research was to make improvements to systems and services. This aligned with Lessick et al's study of health sciences librarians, who considered research to be "very important" for "guidance in evaluating, improving, and initiating new library collections, services, and operations" [3].…”
Section: Automatic Content Analysismentioning
confidence: 69%
See 2 more Smart Citations
“…The survey topic included terms that were seemingly related to decision making, like assess and determine, implying that a primary motivation of librarians who undertook research was to make improvements to systems and services. This aligned with Lessick et al's study of health sciences librarians, who considered research to be "very important" for "guidance in evaluating, improving, and initiating new library collections, services, and operations" [3].…”
Section: Automatic Content Analysismentioning
confidence: 69%
“…The number of hospital librarians' presentations at MLA annual meetings have consistently been much lower than that of academic librarians. Lessick et al found in 2016 that hospital librarians were significantly less likely than their health sciences academic counterparts to engage in research activities, present research at conferences, or write research articles [3]. However, many hospital librarians are very active participants in MLA.…”
Section: Descriptive Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Some institutions will not provide financial support to attend conferences unless the attendee is presenting [ 16 ]. Presenting may be seen as more attainable than publication; surveys consistently show that librarians are more likely to present at a conference than publish a paper [ 11 , 15 , 17 ]. Librarians may consider their conference presentation as the “final product” or, similarly, they may not consider a peer-reviewed article as their “primary desired research output” [ 6 , 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…In other cases, there could be a lack of organizational structure or incentives that encourage publication. A survey of MLA members found that librarians working in hospitals were less likely to present at a conference or publish a paper compared to academic health sciences librarians, especially those pursuing tenure [ 11 ]. Differences in who publishes and what gets published can result in publication bias and limit whose voices are heard.…”
Section: Introductionmentioning
confidence: 99%